Erratum: Reygel, P.C., Willems, W.R. & Artois, T.J. (2011) Koinocystididae and Gnathorhynchidae (Platyhelminthes: Rhabdocoela: Kalyptorhynchia) from the Galapagos, with the description of three new species. Zootaxa, 3096, 27–40. - Reygel, P. C.; Willems, W. R.; Artois, T. J. (Zootaxa, 2011)
(Erratum)